Characterization of Spray Modes and Factors Affecting the Ionization Efficiency of Paper Spray Ionization - Nguyen, Thi Minh Hoa; Song, Woo-Young; Kim, Tae-Young (Frontiers in Chemistry, 2022)
In this study, we systematically evaluated the factors affecting the ionization efficiency of paper spray ionization (PSI), such as electric field, solvent supply rate, and paper thickness and hydrophobicity. The observed paper spray plume was classified into three modes: single cone-jet, multi-jet, and rim-jet modes. With the increase in the spraying voltage, the spray plume appeared in order of single cone-jet, multi-jet, and rim-jet modes. The rim-jet mode exhibited the lowest standard deviation and high ionization efficiency among the three spray modes. The main parameter determining the spray mode was the charge density of the droplets generated by paper spray, which depends on the electric field and solvent supply rate. A thicker paper reduced the electric repulsion between the jets and lowered the threshold voltage to reach the rim-jet mode. Lowering the solvent supply rate caused mode transitions from the single cone-jet to the rim-jet, possibly due to the increased droplet charge density. The hydrophobic modification on a paper substrate led to a different ionization mechanism or electrostatic spray ionization at low applied voltages.